Some Results of Unique Common Fixed Point Generalized In Extended b_2-metric spaces - Sameehah R. Alkaleei; Hakm a T.E.Muostfa (Journal of Pure & Applied Sciences, 2022)
Recently, extended -metric space has been used as a generalization of both -metric and extended metric spaces. The object of this study is to evidence some findings of fixed point and common fixed point for mappings in the frame of extended -metric space, in addition, to generalizing some examples. The outcomes of this study are to generalize and extend some existing findings in previous literature.